PECULIARITIES OF INVOLVING THE URBANIZATION PROCESSES OF ETHNOSES IN RUSSIA - Alexander Alexandrovich Cherkasov (Наука. Инновации. Технологии, 2022)
Territorial development of urbanization in Russia, expressed in regional disparities, imposes its own characteristics on the involvement of different ethnic groups in urbanization processes. On the one hand, one part of the ethnic groups was involved in these processes at earlier stages (Russians, Ukrainians, Belarusians, etc.), the other part of the ethnic groups remained on the "periphery" of urbanization, often preserving the traditional area of settlement, traditional way of life (for example, the titular ethnoses of the North Caucasus). From a scientific point of view, this fact requires special attention, as it is important to know which ethnic groups were involved in the urbanization processes in the early stages of industrial development of the country, signiicantly increasing its share in the structure of the urban population as a "locomotive" of urbanization and what their role in urbanization processes, and in the other hand, it is important to understand which ethnic groups are involved in these processes in the later period and at the present stage. Materials and methods of research: the author defines as the key criteria: the level of urbanization of ethnic groups, which is expressed in the indicator of the proportion of the urban population of the ethnic group from its total population; urbanization transition of ethnic groups, which means overcoming the proportion of the urban population of the ethnic group in 50% of its total population. In the course of the work the method of statistical analysis, and comparative methods that allow the most qualitative analysis of quantitative indicators. A special place is occupied by the use of the cartographic method, which allows to assess the spatial and temporal features of the development of urbanization in the country, including taking into account the peculiarities of the settlement of different ethnic groups. We used census data (Soviet Union) as the initial statistical information of the study 1939, 1959, 1970, 1979, 1989, and RF 2002, 2010). The results of the research and their d the paper proposes a typology of ethnic groups according to the level of urbanization and urban transition. By the nature of participation in the urbanization process, ethnic groups are divided into the following types: the irst type - ethnic groups with an early urbanization transition, whose urbanization transition was recorded by the census of 1959 and earlier (Russians, Ukrainians, Belarusians, Georgians, Uzbeks, Armenians, Moldovans, Azerbaijanis, Latvians, Lithuanians); the second type form ethnic groups, in which the rate of more than 50.0% of living in cities was recorded by the censuses of 1970 and 1979. (Ossetians, Tatars, laktsy, Balkars, Germans); the third type - ethnic groups with late urbanization transition. The urbanization transition was recorded by the population censuses of 1989, 2002 and 2010 (Mordvins, Lezgins, Kumyks, Kalmyks); the Fourth type - ethnic groups with failed urbanization transition by 2010: a) ethnic groups approaching the urbanization transition - the share of the urban population is from 45.1 to 49.9% (Adyghe, Kabardians, Udmurts, Buryats, Bashkirs, etc.); b) ethnic groups with a specific weight of urban population less than 45.0% (Mari, Ingush, Chechens, Dargins, Kazakhs, Yakuts, etc.). The main conclusions and discussion: due to a number of geographical, historical and socio-economic reasons, some ethnic groups were included in the orbit of urban life earlier, others later. Common to all peoples was the tendency of increasing involvement in urbanization processes, while at the present stage a whole group of ethnic groups with a low level of this indicator is allocated.